The Effect of The Probing-Prompting Model on Islamic Eduation Learning Outcomes - Aziza Wati; Dedi Setiawan; Sunarto Sunarto (Assyfa Journal of Islamic Studies, 2026)
This research is motivated by the low learning outcomes of Islamic Religious Education (PAI) among fourth-grade students at SD Negeri 83 Krui Pesisir Barat, caused by conventional teaching models that are monotonous and fail to engage student activity. This study aims to: (1) describe the implementation of the Probing-Prompting learning model; (2) analyze PAI learning outcomes after implementing the model; and (3) examine the effect of the Probing-Prompting model on PAI learning outcomes. A quantitative method with a quasi-experimental design (nonequivalent control group) was employed. The population consisted of all fourth-grade students (64 students), with class IV A as the control group (21 students) and class IV B as the experimental group (21 students), selected using cluster sampling. The instrument was a validated multiple-choice test (10 valid items, reliability 0.680). Data analysis techniques included normality test (Shapiro-Wilk), homogeneity test (Levene), and hypothesis test (independent sample t-test). The results showed: (1) the implementation of the Probing-Prompting model proceeded well through the syntax of presenting students with new situations, providing guiding and probing questions, and reinforcing material; (2) learning outcomes of the experimental group (post-test mean 81.74) were higher than those of the control group (post-test mean 71.30); (3) the hypothesis test showed a significance value (2-tailed) of 0.002 < 0.05, thus Ha was accepted. This study concludes that the Probing-Prompting learning model has a positive and significant effect on PAI learning outcomes of fourth-grade students at SD Negeri 83 Krui Pesisir Barat.